Meningkatkan Deteksi Tumbuh Kembang Melalui Program Edukasi Keluarga - Hadi Guawan; Zahida Azzahra; Perdina Rantika Nasution; Arnis Syanti; Nurlianti Nurlianti; Diva Trisna Hartaty (Inovasi Pendidikan dan Anak Usia Dini, 2026)
Early detection of child growth and development is a crucial effort to prevent developmental delays and health problems in children. Family involvement plays a significant role because the family is the closest environment to the child and has continuous interaction in daily life. This study aims to analyze the effectiveness of a family education program in improving parents’ knowledge and skills in detecting child growth and development. The research employed a quantitative approach with a quasi-experimental design using a pretest–posttest method. The population consisted of families with children aged 0–6 years, with samples selected using purposive sampling techniques. Data were collected through questionnaires and observation sheets measuring parents’ knowledge, attitudes, and skills related to growth and developmental detection. Data analysis was conducted using paired sample t-tests. The results showed a significant increase in parents’ knowledge and skills after participating in the family education program. The findings indicate that structured and continuous family education can enhance parents’ ability to monitor child growth and development independently. This study implies that family-based education programs can be integrated into community health services as a preventive strategy to improve child health outcomes.